PREVALENSI KOMPLIKASI MAKROVASKULER DAN MIKROVASKULER PADA PENYANDANG DIABETES MELITUS - Suryanti, Suryanti; Duwi Pudjiati (Medical Journal of Nusantara, 2025)
Background: DM is a disease caused by metabolic disorders. DM sufferers who do not carry out treatment and care properly will experience complications at both the cellular and anatomical levels, both macrovascular and microvascular. Macrovascular complications are blockages in large blood vessels such as in the heart and brain which often result in death and in the lower extremities which result in gangrene in the legs, while microvascular complications are blockages in small blood vessels such as in the kidneys and in the eyes causing vision problems. Objective: The research aims to determine the number of macrovascular and microvascular complications in people with DM at Prolanis Daun Salam Sibela Health Center. And the influence of Diabetes Mellitus on macrovascular and microvascular complications Methods: Descriptive research type with cross sectional design. The population was people with diabetes mellitus who participated in Prolanis Daun Salam at Sibela Health Center using total sampling. The data collection technique is by means of anamnese, interview, questionnaire, early detection of macrovascular and microvascular complications. The data analysis technique uses the chi-square statistical test to analyze data on categories of macrovascular and microvascular complications, and determine the relationship or trend of macrovascular complications and microvascular complications. Results: The most macrovascular complications were complications in peripheral disease, namely 87%, and the smallest were cardiovascular complications at 13%, and cerebrovascular complications at 37%. Meanwhile, microvascular complications in retinopathy accounted for 27%, neuropathy accounted for 30% and the most common was nephropathy at 47% Conclusion: DM sufferers at Prolanis Daun Salam Sebela Community Health Center are at risk of developing macrovascular and microvascular complications